PENGARUH PENERIMAAN, PENEMPATAN KERJA, DAN KOMPETENSI KARYAWAN LOKAL BATURAJA TERHADAP KINERJA KARYAWAN DIVISION OPERATION PT. SEMEN BATURAJA (PERSERO) TBK - Ahmad Haikal; Luis Marnisah; Jefirstson Richset Riwu Kore (Fakultas Pertanian, 2022)
This study aims to analyze and prove the effect of work experience, level of education and training on the performance of employees of PT Semen Baturaja (persero) Tbk in the Operations Division, either partially or simultaneously. The population of this study were 286 employees of PT Semen Baturaja (Persero) Tbk in the Operations Division with a sample of 127 employees. The sampling technique used is non-probability sampling with purposive sampling. The results showed that the t-value of the work experience variable (4.204) > t-table (1.97944), the t-value of the education level variable (4.218) > t-table (1.97944), the t-count of the training variable (6.067) > t-table (1 , 9746) and Fcount value (65.117) > Ftable (2.68). The correlation coefficient (R) 0.783 shows a strong and positive relationship, the coefficient of determination (R2) is 0.614 which means 61.4% of the employee performance variables at PT Semen Baturaja (Persero Tbk in the Operations Division) can be explained by variables of work experience, level of education and training and 38 .6% is influenced by other variables. The conclusion of this study shows that the variables of work experience, level of education and training partially and significantly have a positive and significant effect on employee performance.